2013
DOI: 10.1186/1743-422x-10-170
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Newcastle disease virus in Pakistan: a countrywide perspective

Abstract: BackgroundNewcastle disease (ND) is one of the most deadly diseases of poultry around the globe. The disease is endemic in Pakistan and recurrent outbreaks are being reported regularly in wild captive, rural and commercial poultry flocks. Though, efforts have been made to characterize the causative agent in some of parts of the country, the genetic nature of strains circulating throughout Pakistan is currently lacking.Material and methodsTo ascertain the genetics of NDV, 452 blood samples were collected from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 30 publications
4
25
0
Order By: Relevance
“…Studies on NDV pathotyping in countries bordering Iran have also revealed the presence of virulent strains. In Turkey, virulent NDVs were isolated among the wild bird population in the Lake Van basin by analyzing for virulent F protein using real time RT-PCR (rRT-PCR) (25) (27,28). Our results are in agreement with previous studies reporting the detection of virulent NDVs in Iran (10,12).…”
Section: Discussionsupporting
confidence: 83%
“…Studies on NDV pathotyping in countries bordering Iran have also revealed the presence of virulent strains. In Turkey, virulent NDVs were isolated among the wild bird population in the Lake Van basin by analyzing for virulent F protein using real time RT-PCR (rRT-PCR) (25) (27,28). Our results are in agreement with previous studies reporting the detection of virulent NDVs in Iran (10,12).…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, the inability of live vaccines to elicit a protective immune response might be due to an inadequate cold chain supply system, inappropriate route of vaccination, or incorrect vaccination schedules. It has been reported that the currently applied AAVV-1 vaccines give better protection against the velogenic AAVV-1 s isolated from the 1930s through to the 1970s (Herts33/56, California 71) than those more recently isolated [38]. Hence parameters for selection of vaccine strains need to be reconsidered.…”
Section: Discussionmentioning
confidence: 99%
“…Co-infections were common for AIV and AAVV-1 (9 AIV/ AAVV-1 coinfected flocks) but less common for the other avian viruses of interest (Table 1). Briefly, 9 flocks (6,21,23,38,41,42,66,67,68) were found positive for AIV (H9) and AAVV-1 coinfections. AAVV-1 + aMPV, AIV + aMPV and AAVV-1 + IBV coinfections were detected only in flock number 69, 70 and 80, respectively.…”
Section: Virus Prevalence and Co-infections In Pakistanis Farmsmentioning
confidence: 99%
“…Immune responses to ND vaccines are influenced by routes (ocular, injection, drinking water, aerosol or nasal) of vaccination. Eye drop vaccination stimulates Harderian gland to produce local antibodies (Shabbir et al 2013). Vaccines given through mucosal surfaces (eye drop and nasal) generate mucosal immune response.…”
Section: Introductionmentioning
confidence: 99%